Treasure Island - Harrar, Andrew (Campfire graphic novels. Classic., 2010)
Retells in graphic novel format Stevenson's story of how Jim Hawkins and his innkeeper mother find a treasure map that leads them to a pirate's fortune while going through the possessions of a deceased guest who owed them money.